Evaluation of Clinical Decision-Making Quality in Catastrophic Emergency Management at Primary Care Services in Pagar Jati Community Health Center, 2023 - Elias Siahaan (Medistra Medical Journal (MMJ), 2025)
Background: The quality of clinical decision-making is a crucial factor in managing catastrophic emergencies, particularly in primary care facilities that serve as the frontline of disaster response. Pagar Jati Community Health Center, as a primary health service, needs to be evaluated for its capacity to make rapid, accurate, and well-coordinated clinical decisions during disaster situations. Objective: This study aims to evaluate the quality of clinical decision-making among healthcare workers in managing catastrophic emergencies at Pagar Jati Community Health Center in 2023. Methods: This research employed a descriptive-analytic design with a quantitative approach. The sample consisted of medical personnel (doctors, nurses, and midwives) involved in emergency management. Data were collected through structured questionnaires, simulation observations, and a review of standard operating procedures (SOPs). Descriptive analysis was performed to assess timeliness, clinical accuracy, and team coordination. Results: The study found that most clinical decisions were made within ≤10 minutes, consistent with the golden time standard, although 23% of cases experienced delays due to communication barriers. Clinical accuracy reached 78% in accordance with national guidelines, but errors were identified in prioritizing patients with multiple injuries. Internal team coordination among healthcare workers was relatively good, yet external coordination with referral hospitals faced challenges, particularly in communication and the timely evacuation of critical patients. Conclusion: The quality of clinical decision-making at Pagar Jati Community Health Center is considered adequate but requires improvement through regular disaster simulation training, strengthening of referral communication systems, and the development of integrated emergency information systems. These efforts are expected to enhance the effectiveness of catastrophic emergency management in primary care services.